Where is my organ? Organ donation with blockchain system - Ahmad Firdaus, Zainal Abidin; Yew Khen, Yong; Mohd Faizal, Ab Razak; Wan Isni Sofiah, Wan Din; Mohd Zamri, Osman; Che Akmal, Che Yahaya (2021)
Organ donation information is importance to save someone’ s life. It is because the timelinessof the data will help patient to find suitable organ faster. Besides that, the data must consistence and accurate among the data communication process. Therefore, decentralized data storage is the most suitable way to store the data because of the characteristics of the storage. The Organ Management System nowadays is using client-server system. This kind of system is storing data in server means that if the server is failure, the data will be lost and hard to recover back. This project is proposing a blockchain based organ donation management system in order to fix the problem of clientserver system.